(untitled) (Modern education and development, 2025)
The article presents how artificial intelligence technologies can be integrated into the educational process in technical schools and its role in improving the quality of education. The article also shows the importance of automatic assessment based on SI, the ability of teachers to effectively manage time and resources, and analytical approaches in analyzing the quality of education. The article concludes with the role of artificial intelligence in further improving the education system in technical schools in the future.